PENGARUH GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP HARGA SAHAM PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2016 - Na’am Chusaeri; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT This study aims to determine the effect of good corporate governance and disclosure of corporate social responsibility on the stock prices of companies listed on the Indonesia Stock Exchange (IDX) for the period of 2014-2016. The type of data used in this study is secondary data consisting of qualitative and quantitative data. The method used in this study purposive sampling technique. This study uses multiple regression analysis by SPSS 17 Version. The results show that 1) there is an influence of good corporate governance and disclosure of corporate social responsibility partially on the stock prices of companies listed on the Indonesia Stock Exchange (IDX) for the period of 2014-2016, 2) there are influences of good corporate governance and disclosure of corporate social responsibility simultaneously on the stock price of companies listed on the Indonesia Stock Exchange (IDX) for the period of 2014-2016, 3) Disclosure of corporate social responsibility has a dominant influence on the stock price of companies listed on the Indonesia Stock Exchange (IDX) for the period of 2014-2016.Keywords: Corporate Governance, Corporate Social Responsibility, Stock Prices